WC-TiC-Mo2C-carbonfiber-8Co hard alloy and preparation method thereof
By adding carbon fiber to WC cemented carbide and adopting high-temperature and high-pressure sintering process, WC-TiC-Mo2C-carbon fiber-8Co cemented carbide with high hardness and high toughness was prepared, which solved the problem of insufficient mechanical properties of existing cemented carbides and significantly improved its mechanical properties.
Patent Information
- Application Number
- CN202411779619.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-11
AI Technical Summary
There are still shortcomings in the existing WC cemented carbide in improving mechanical properties such as hardness and toughness, which affects its stability and expansion of its application range in cutting applications.
WC-TiC-Mo2C-carbon fiber-8Co carbide is used and prepared through high-temperature and high-pressure sintering process. The specific steps include pre-pressing and sintering under high-temperature and high-pressure conditions.
By introducing carbon fibers into cemented carbide and adopting high-temperature and high-pressure sintering method, the hardness and toughness of cemented carbide are significantly improved, and its density and bonding phase distribution uniformity are enhanced, thereby improving the overall mechanical properties.
Smart Images

Figure CN119800139A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hard alloy preparation, in particular to a WC-TiC-Mo2C-carbon fiber-8Co hard alloy and a preparation method thereof. Background Art
[0002] Cemented carbide is defined as a composite material containing a high volume fraction of a hard phase (WC, TiC, TaC, etc.) embedded in a metal binding phase (i.e., Co, Fe, Ni). It plays an important role in cutting, drilling, mining processing, and wear-resistant parts because of its good hardness, strength, toughness, excellent wear resistance, and corrosion resistance. How to further improve the hardness, toughness and other mechanical properties of WC cemented carbide is of great significance to its stability in cutting applications and the expansion of its application range.
[0003] The methods for improving the hardness and toughness of WC cemented carbide in the prior art mainly include: introducing suitable additives, refining WC grains, and strengthening the metal bonding phase; changing the composition of the metal bonding phase or adding alloying elements to improve the wettability with the hard phase to improve the sintering performance; optimizing the preparation process, adopting a new sintering method, reducing the porosity and defects of the alloy, so as to achieve the performance indicators of engineering applications, etc.
[0004] For example, the applicant has previously applied for a Chinese invention patent with publication number CN 110205535 A, entitled A method for preparing cemented carbide. The preparation method comprises weighing nano WC powder and Co powder according to a ratio, adding 0.4-0.8% by mass of a composite grain inhibitor and 0.2-0.8% by mass of carbon nanotubes or nano carbon fibers as reinforcing materials, mixing and drying, and then sintering by spark plasma sintering equipment to finally obtain ultrafine or nano cemented carbide; the density, hardness (HRA) and flexural strength of the cemented carbide are improved to a certain extent compared with the cemented carbide prepared by the traditional sintering method, but how to further improve the mechanical properties such as hardness and toughness of the cemented carbide is still the research direction of the current cemented carbide preparation technology and a problem to be solved urgently. Summary of the invention
[0005] The present invention aims to provide a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide and a preparation method thereof, so as to further improve the mechanical properties such as hardness and toughness of the cemented carbide.
[0006] In order to achieve the above-mentioned object, the specific scheme adopted by the present invention is: a preparation method of WC-TiC-Mo2C-carbon fiber-8Co cemented carbide, comprising the following steps: S1: mixing tungsten carbide, cobalt, titanium carbide, molybdenum carbide and carbon fiber to obtain a mixed powder; S2: pre-pressing the mixed powder to obtain a cemented carbide intermediate; S3: Sintering the cemented carbide intermediate under high temperature and high pressure to obtain the WC-TiC-Mo2C-carbon fiber-8Co cemented carbide; wherein the conditions for high temperature and high pressure sintering are: sintering temperature 1300-1450°C, sintering pressure 2-6GPa, and insulation time 2-10min.
[0007] As a further optimization of the above technical solution: in the mixed powder, the mass percentage of each component is: tungsten carbide 83.17-84.00%, titanium carbide 5.89-6.00%, molybdenum carbide 1.98-2.00%, cobalt 7.92-8.00%, and carbon fiber 0.20-1.00%.
[0008] As a further optimization of the above technical solution: high temperature and high pressure sintering is carried out in a six-sided top press.
[0009] As a further optimization of the above technical solution: Step S1 is specifically: taking tungsten carbide, cobalt, titanium carbide, molybdenum carbide and carbon fiber as powder raw materials, putting them into a ball mill together with anhydrous ethanol and cemented carbide balls for ball milling and mixing, and drying to obtain a mixed powder.
[0010] As a further optimization of the above technical solution: the sizes of the powder raw materials are: tungsten carbide particle size 10-200nm, cobalt particle size 10-100nm, titanium carbide particle size 10-200nm, molybdenum carbide particle size 10-200nm, carbon fiber diameter 1-20nm, length 2-100μm.
[0011] As a further optimization of the above technical solution: during the ball milling mixing process, the mass ratio of cemented carbide balls to powder raw materials is 5:1.
[0012] As a further optimization of the above technical solution: the ball milling mixing is carried out in a high-energy ball mill, a drum ball mill or a grinding mill.
[0013] As a further optimization of the above technical solution: the ball milling mixing time is 12-24h.
[0014] As a further optimization of the above technical solution: the drying temperature after ball milling mixing is 60-90°C, and the drying time is 8-24h.
[0015] A WC-TiC-Mo2C-carbon fiber-8Co hard alloy is prepared by any of the above preparation methods.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention adds carbon fiber in situ and sinters the sample block by high temperature and high pressure method, thereby obtaining WC-TiC-Mo2C-carbon fiber-8Co cemented carbide with both high hardness and high toughness. The sintered sample block material has higher density and more uniform distribution of bonding phase, further optimizing the microstructure of the sample.
[0018] The present invention adopts a high-temperature and high-pressure sintering method to prepare cemented carbide, which can effectively promote the densification of the alloy. During the sintering process, the addition of carbon fiber can inhibit the growth of WC grains. High-pressure sintering is adopted while adding carbon fiber. The high pressure promotes the continuous adjustment of the structure of the carbon fiber, and the arrangement of the carbon layer is more orderly, thereby improving the microstructure of the cemented carbide matrix, further improving the toughening effect of the carbon fiber on the alloy, and improving the overall mechanical properties of the cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a 50,000-fold scanning electron microscope image of the cemented carbide in Example 2;
[0020] Figure 2 This is a 50,000-fold scanning electron microscope image of the cemented carbide in Example 4. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts not described and disclosed in detail in the following embodiments of the present invention should be understood as the prior art known or should be known to those skilled in the art, such as the specific structure and use method of the six-sided top press, high-energy ball mill, drum ball mill and grinder.
[0022] Example 1
[0023] S1: Weigh 83.83% by mass of tungsten carbide, 7.98% by mass of cobalt, 5.99% by mass of titanium carbide, 2.00% by mass of molybdenum carbide and 0.20% by mass of carbon fiber, mix and dry to obtain a mixed powder;
[0024] Specifically, 13.412 g of tungsten carbide with a particle size of 180 nm, 1.277 g of cobalt with a particle size of 50 nm, 0.958 g of titanium carbide with a particle size of 180 nm, 0.320 g of molybdenum carbide with a particle size of 180 nm and 0.032 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill with 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 80 ° C for 8 h to obtain a mixed powder;
[0025] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0026] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1300°C, a holding time of 6 min, a sintering pressure of 6 GPa, and a vacuum condition (≤1×10 -2 Pa) to obtain WC-TiC-Mo2C-carbon fiber-8Co cemented carbide.
[0027] The prepared WC-TiC-Mo2C-carbon fiber-8Co cemented carbide was recorded as sample 1, and its performance was tested: the grains of sample 1 were fine and the morphology was relatively regular, the Vickers hardness was HV 2210.5, and the fracture toughness was K IC 12.5MPa·m 1 / 2 , density is 14.37 g·cm -3 .
[0028] Example 2
[0029] S1: Weigh 83.67% by mass of tungsten carbide, 7.97% by mass of cobalt, 5.97% by mass of titanium carbide, 1.99% by mass of molybdenum carbide and 0.40% by mass of carbon fiber, mix and dry to obtain a mixed powder;
[0030] Specifically, 13.387 g of tungsten carbide with a particle size of 180 nm, 1.275 g of cobalt with a particle size of 80 nm, 0.955 g of titanium carbide with a particle size of 180 nm, 0.318 g of molybdenum carbide with a particle size of 180 nm and 0.064 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill with 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 60 ° C for 12 h to obtain a mixed powder;
[0031] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0032] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1400°C, a holding time of 6 min, a sintering pressure of 4 GPa, and a vacuum condition (≤1×10 -2 Pa), that is, WC-TiC-Mo2C-carbon fiber-8Co cemented carbide is obtained.
[0033] The prepared WC-TiC-Mo2C-carbon fiber-8Co cemented carbide was recorded as sample 2, and its performance was tested: the microstructure of sample 2 was uniform and had fewer pores and defects, the Vickers hardness was HV 2229.9, and the fracture toughness was K IC 12.4MPa·m 1 / 2 , density is 14.46 g·cm -3 .
[0034] Example 3
[0035] S1: Weigh 83.50% by mass of tungsten carbide, 7.95% by mass of cobalt, 5.96% by mass of titanium carbide, 1.99% by mass of molybdenum carbide and 0.60% by mass of carbon fiber, mix and dry to obtain a mixed powder;
[0036] Specifically, 13.360 g of tungsten carbide with a particle size of 150 nm, 1.272 g of cobalt with a particle size of 80 nm, 0.954 g of titanium carbide with a particle size of 150 nm, 0.318 g of molybdenum carbide with a particle size of 150 nm and 0.096 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill with 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 60 ° C for 8 h to obtain a mixed powder;
[0037] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0038] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1450°C, a holding time of 6 min, a sintering pressure of 4 GPa, and a vacuum condition (≤1×10 -2 Pa), that is, WC-TiC-Mo2C-carbon fiber-8Co cemented carbide is obtained.
[0039] The prepared WC-TiC-Mo2C-carbon fiber-8Co cemented carbide was recorded as sample 3, and its performance was tested: Sample 3 had fine grains, uniform structure, Vickers hardness of HV 2237.4, and fracture toughness of K IC 13.5MPa·m 1 / 2 , density is 14.59 g·cm -3 .
[0040] Example 4
[0041] S1: Weigh 83.33% by mass of tungsten carbide, 7.94% by mass of cobalt, 5.95% by mass of titanium carbide, 1.98% by mass of molybdenum carbide and 0.80% by mass of carbon fiber, mix and dry them to obtain a mixed powder;
[0042] Specifically, 13.333 g of tungsten carbide with a particle size of 180 nm, 1.270 g of cobalt with a particle size of 80 nm, 0.952 g of titanium carbide with a particle size of 180 nm, 0.317 g of molybdenum carbide with a particle size of 180 nm and 0.128 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill with 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 80 ° C for 12 h to obtain a mixed powder;
[0043] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0044] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1350°C, a holding time of 6 min, a sintering pressure of 3 Gpa, and a vacuum condition (≤1×10 -2 Pa), that is, WC-TiC-Mo2C-carbon fiber-8Co cemented carbide is obtained.
[0045] The prepared WC-TiC-Mo2C-carbon fiber-8Co cemented carbide was recorded as sample 4, and its performance was tested: sample 4 had fine grains, uniform structure, Vickers hardness of HV 2223.8, and fracture toughness of K IC 13.1MPa·m 1 / 2 , density is 14.31 g·cm -3 .
[0046] Example 5
[0047] S1: Weigh 83.17% by mass of tungsten carbide, 7.92% by mass of cobalt, 5.93% by mass of titanium carbide, 1.98% by mass of molybdenum carbide and 1.00% by mass of carbon fiber, mix and dry to obtain a mixed powder;
[0048] Specifically, 13.301 g of tungsten carbide with a particle size of 150 nm, 1.267 g of cobalt with a particle size of 50 nm, 0.949 g of titanium carbide with a particle size of 150 nm, 0.317 g of molybdenum carbide with a particle size of 150 nm and 0.160 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill with 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 80 ° C for 12 h to obtain a mixed powder;
[0049] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0050] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1380°C, a holding time of 6 min, a sintering pressure of 5 Gpa, and a vacuum condition (≤1×10 -2 Pa), that is, WC-TiC-Mo2C-carbon fiber-8Co cemented carbide is obtained.
[0051] The prepared WC-TiC-Mo2C-carbon fiber-8Co cemented carbide was recorded as sample 5, and its performance was tested: sample 5 had fine grains, uniform structure, Vickers hardness of HV 2222.1, and fracture toughness of K IC 12.3MPa·m 1 / 2, density is 14.25 g·cm -3 .
[0052] Comparative Example 1
[0053] S1: Weigh 84.00% by mass of tungsten carbide, 8.00% by mass of cobalt, 6.00% by mass of titanium carbide and 2.00% by mass of molybdenum carbide according to the proportion, mix and dry to obtain a mixed powder;
[0054] Specifically, 13.440 g of tungsten carbide with a particle size of 150 nm, 1.280 g of cobalt with a particle size of 50 nm, 0.960 g of titanium carbide with a particle size of 150 nm, and 0.320 g of molybdenum carbide with a particle size of 150 nm were weighed, put into a ball mill jar of a drum ball mill with 80 g of cemented carbide balls and 50 ml of anhydrous ethanol, mixed evenly for 24 h, and dried in a drying oven at 80 ° C for 8 h to obtain a mixed powder;
[0055] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0056] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1450°C, a holding time of 10 min, a sintering pressure of 4 GPa, and a vacuum condition (≤1×10 -2 Pa), and WC-TiC-Mo2C-8Co cemented carbide was obtained.
[0057] The prepared WC-TiC-Mo2C-8Co cemented carbide was recorded as comparative sample 1, and its performance was tested: the grains of comparative sample 1 had a small amount of pores and defects, the Vickers hardness was HV 2065.9, and the fracture toughness was K IC 10.3MPa·m 1 / 2 , density is 14.19 g·cm -3 .
[0058] Comparative Example 2
[0059] S1: Weigh 83.50% by mass of tungsten carbide, 7.95% by mass of cobalt, 5.96% by mass of titanium carbide, 1.99% by mass of molybdenum carbide and 0.60% by mass of carbon fiber, mix and dry them to obtain a mixed powder;
[0060] Specifically, 13.360 g of tungsten carbide with a particle size of 180 nm, 1.272 g of cobalt with a particle size of 80 nm, 0.954 g of titanium carbide with a particle size of 180 nm, 0.318 g of molybdenum carbide with a particle size of 180 nm, and 0.096 g of carbon fiber with a diameter of 1-20 nm and a length of 2-100 μm were weighed, put into a ball mill jar of a drum ball mill, 80 g of carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 80 ° C for 8 h to obtain a mixed powder;
[0061] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0062] S3: The cemented carbide intermediate is placed in a tubular furnace and sintered in an argon atmosphere at a sintering temperature of 1350° C. The sintering process is not pressurized and the holding time is 15 minutes to obtain WC-TiC-Mo2C-carbon fiber-8Co cemented carbide.
[0063] The prepared WC-TiC-Mo2C-8Co cemented carbide was recorded as comparative sample 2, and its performance was tested: the grain morphology of comparative sample 2 was irregular, the structure was uneven, the Vickers hardness was HV 2010.9, and the fracture toughness was K IC 10.1MPa·m 1 / 2 , density is 14.26 g·cm -3 .
[0064] Comparative Example 3
[0065] S1: Weigh 84.00% by mass of tungsten carbide, 8.00% by mass of cobalt, 6.00% by mass of titanium carbide and 2.00% by mass of molybdenum carbide according to the proportion, mix and dry to obtain a mixed powder;
[0066] Specifically, 13.440 g of tungsten carbide with a particle size of 180 nm, 1.280 g of cobalt with a particle size of 80 nm, 0.960 g of titanium carbide with a particle size of 180 nm, and 0.320 g of molybdenum carbide with a particle size of 180 nm were weighed, put into a ball mill jar of a drum ball mill with 80 g of cemented carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 80 ° C for 8 h to obtain a mixed powder;
[0067] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0068] S3: The cemented carbide intermediate is placed in a tubular furnace and sintered in an argon atmosphere at a sintering temperature of 1350° C. The sintering process is not pressurized and the holding time is 15 minutes to obtain a WC-TiC-Mo2C-8Co cemented carbide.
[0069] The prepared WC-TiC-Mo2C-8Co cemented carbide was recorded as comparative sample 3, and its performance was tested: the comparative sample 3 had a larger grain size and an uneven structure, a Vickers hardness of HV 1964.2, and a fracture toughness of K IC 9.4MPa·m 1 / 2 , density is 14.04 g·cm -3 .
[0070] Comparative Example 4
[0071] S1: Weigh 83.50% by mass of tungsten carbide, 7.95% by mass of cobalt, 5.96% by mass of titanium carbide, 1.99% by mass of molybdenum carbide and 0.60% by mass of carbon nanotubes, mix and dry to obtain a mixed powder;
[0072] Specifically, 13.360 g of tungsten carbide with a particle size of 150 nm, 1.272 g of cobalt with a particle size of 80 nm, 0.954 g of titanium carbide with a particle size of 150 nm, 0.318 g of molybdenum carbide with a particle size of 150 nm and 0.096 g of carbon nanotubes were weighed, put into a ball mill jar of a drum ball mill with 80 g of cemented carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 60 ° C for 8 h to obtain a mixed powder;
[0073] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0074] S3: The cemented carbide intermediate is placed in a six-sided top press for sintering at a sintering temperature of 1450°C, a holding time of 8 min, a sintering pressure of 4 Gpa, and a vacuum condition (≤1×10 -2 Pa), and WC-TiC-Mo2C-carbon nanotube-8Co cemented carbide was obtained.
[0075] The prepared WC-TiC-Mo2C-carbon nanotube-8Co cemented carbide was recorded as comparative sample 4, and its performance was tested: the grain morphology of comparative sample 4 showed diversity, with many pores and defects, the Vickers hardness was HV 2076.9, and the fracture toughness was K IC 12.9MPa·m 1 / 2 , density is 14.91 g·cm -3 .
[0076] Comparative Example 5
[0077] S1: Weigh 83.50% by mass of tungsten carbide, 7.95% by mass of cobalt, 5.96% by mass of titanium carbide, 1.99% by mass of molybdenum carbide and 0.60% by mass of carbon nanotubes, mix and dry to obtain a mixed powder;
[0078] Specifically, 13.360 g of tungsten carbide with a particle size of 150 nm, 1.272 g of cobalt with a particle size of 80 nm, 0.954 g of titanium carbide with a particle size of 150 nm, 0.318 g of molybdenum carbide with a particle size of 150 nm and 0.096 g of carbon nanotubes were weighed, put into a ball mill jar of a drum ball mill with 80 g of cemented carbide balls and 50 ml of anhydrous ethanol, uniformly mixed for 24 h, and dried in a drying oven at 60 ° C for 8 h to obtain a mixed powder;
[0079] S2: Laying the mixed powder in a mold and pre-pressing it to obtain a cemented carbide intermediate;
[0080] S3: placing the cemented carbide intermediate into a tubular furnace for sintering at a sintering temperature of 1450° C. for 8 min without applying pressure during the sintering process, thereby obtaining a WC-TiC-Mo2C-carbon nanotube-8Co cemented carbide.
[0081] The prepared WC-TiC-Mo2C-carbon nanotube-8Co cemented carbide was recorded as comparative sample 5, and its performance was tested: the Vickers hardness of comparative sample 5 was HV 2044.2, and the fracture toughness was K IC 11.2MPa·m 1 / 2 , density is 14.32 g·cm -3 .
[0082] Next, the properties of the cemented carbides prepared in the examples and comparative examples are analyzed: For ease of understanding, the sintering method using a sintering pressure of 2-6 GPa as used in the examples is referred to as high pressure sintering.
[0083] Taking fracture toughness as an example, the comparative example and the embodiment are compared:
[0084] Comparative Example 3 did not add carbon fiber and adopted a non-pressurized sintering method (i.e., high-pressure sintering was not adopted). The fracture toughness of the obtained comparative sample 3 was K IC 9.4MPa·m 1 / 2 Comparative Example 1 only uses high pressure sintering, but no carbon fiber is added to the raw material. The fracture toughness of the obtained comparative sample 1 is K IC 10.3MPa·m 1 / 2 Compared with the comparative sample 3, the fracture toughness increased by 0.9MPa·m 1 / 2 ; In Comparative Example 2, carbon fiber is added to the raw material, but high pressure sintering is not used. The fracture toughness of the comparative sample 2 is K IC 10.1MPa·m 1 / 2 Compared with the comparative sample 3, the fracture toughness increased by 0.7 MPa·m 1 / 2 ; Example 3 uses high pressure sintering, and carbon fiber is added to the raw material. The fracture toughness of sample 3 is K IC13.5MPa·m 1 / 2 Compared with the comparative sample 3, the fracture toughness increased by 4.1MPa·m 1 / 2 ;
[0085] It can be seen that the fracture toughness of the sample obtained in Example 3 is greater than that of the samples obtained in Comparative Examples 1-3. At the same time, the fracture toughness increase of Example 3 compared with Comparative Example 3 (4.1 MPa·m 1 / 2 ) is greater than the sum of the increases in fracture toughness of Comparative Example 1 and Comparative Example 2 (0.9 MPa·m 1 / 2 +0.7MPa·m 1 / 2 =1.6MPa·m 1 / 2 ), indicating that in the process of preparing cemented carbide in Example 3, high pressure sintering further improves the toughening effect of carbon fiber.
[0086] Similarly, from the analysis of the Vickers hardness, it can be seen that the Vickers hardness of the sample obtained in Example 3 is greater than the Vickers hardness of the samples obtained in Comparative Examples 1-3. At the same time, the Vickers hardness of Example 3 is increased by (273.2) compared with that of Comparative Example 3, which is greater than the sum of the increases in the Vickers hardness of Comparative Example 1 and Comparative Example 2 (101.7+46.7=148.4), indicating that in the process of preparing cemented carbide in Example 3, high pressure sintering further improves the effect of carbon fiber on improving the hardness of the alloy.
[0087] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing WC-TiC-Mo2C-carbon fiber-8Co cemented carbide, characterized in that: The following steps are involved: S1: mixing tungsten carbide, cobalt, titanium carbide, molybdenum carbide and carbon fiber to obtain a mixed powder; S2: pre-pressing the mixed powder to obtain a cemented carbide intermediate; S3: Sintering the cemented carbide intermediate under high temperature and high pressure to obtain the WC-TiC-Mo2C-carbon fiber-8Co cemented carbide; wherein the conditions for high temperature and high pressure sintering are: sintering temperature 1300-1450°C, sintering pressure 2-6GPa, and insulation time 2-10min.
2. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 1, characterized in that: In the mixed powder, the mass percentage of each component is: 83.17-84.00% of tungsten carbide, 5.89-6.00% of titanium carbide, 1.98-2.00% of molybdenum carbide, 7.92-8.00% of cobalt, and 0.20-1.00% of carbon fiber.
3. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 1, characterized in that: High temperature and high pressure sintering is carried out in a six-sided top press.
4. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 1, characterized in that: Step S1 specifically comprises: taking tungsten carbide, cobalt, titanium carbide, molybdenum carbide and carbon fiber as powder raw materials, putting them into a ball mill together with anhydrous ethanol and cemented carbide balls for ball milling and mixing, and drying to obtain a mixed powder.
5. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 4, characterized in that: The sizes of the powder raw materials are: tungsten carbide particle size 10-200nm, cobalt particle size 10-100nm, titanium carbide particle size 10-200nm, molybdenum carbide particle size 10-200nm, carbon fiber diameter 1-20nm, length 2-100μm.
6. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 4, characterized in that: During the ball milling mixing process, the mass ratio of cemented carbide balls to powder raw materials was 5:
1.
7. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 4, characterized in that: The ball milling mixing is carried out in a high energy ball mill, a drum ball mill or a grinding mill.
8. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 4, characterized in that: The ball milling mixing time is 12-24h.
9. The method for preparing a WC-TiC-Mo2C-carbon fiber-8Co cemented carbide according to claim 4, characterized in that: The drying temperature after ball milling is 60-90°C and the drying time is 8-24h.
10. A WC-TiC-Mo2C-carbon fiber-8Co cemented carbide, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of hard alloy
CN110205535A
Cited By
Multi-component composite hard alloy and preparation method thereof
CN122382394A
Multicomponent cemented carbide and method for producing the same
CN122382394B